A Novel Secretory Factor, Neurogenesin-1, Provides Neurogenic Environmental Cues for Neural Stem Cells in the Adult Hippocampus - Ueki, Takatoshi (J Neurosci, 2003)
Neurogenesis occurs in restricted regions in the adult mammalian brain, among which the neurogenesis in the hippocampal dentate gyrus plays the crucial role in learning and memory. To date, little is known about neurogenic cues, which result in the neuronal fate adoption of neural stem cells residing in neurogenic regions, especially neurogenic cues in adult hippocampal neurogenesis. In the present study, we show that hippocampal astrocytes and also dentate granule cells adjacent to neural stem cells secrete a newly cloned novel secretory factor, Neurogenesin-1. This protein contains three cysteine-rich domains and a unique sequence and contributes to neuronal differentiation of neural stem cells in the adult brain by preventing the adoption of a glial fate. Furthermore, the neurogenic activity detected in the hippocampal culture medium was markedly suppressed by the administration of an anti-Neurogenesin-1 antibody. These findings suggest endogenous mechanisms that induce adult hippocampal neurogenesis and propose an innovative treatment for the neurodegenerative diseases that cause loss of hippocampal neurons.